Maqashid Sunnah as a Philosophical Foundation for Developing Progressive Islamic Education in the Digital Era - Masyhari, Mohammad Ridlo; Bin Jamil, Khairil Husaini (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2024)
This article aims to look at the philosophy of Islamic education from the perspective of maqashid sunnah (the ultimate purpose of hadith) in the social sphere to produce progressive Islamic education in the digital era. The digital era is characterized by a very wide openness of information, causing competition in this era to be very tight, so competitive and productive human qualities are needed, and this can be produced from a progressive pattern of Islamic education. Unfortunately, Islamic education as an instrument for human development, currently focuses more on developing each student to achieve high skills and qualifications. Still, on the other hand, it can be seen that the output of this is humans who focus more on profits for themselves. It does not have much influence on people's lives, even though progress in its true meaning should be oriented towards the benefits of the wider community. For this reason, studies are needed to examine the philosophical basis of education to find solutions to the problems above. As a source of Islamic teachings, Hadith has a core purpose, maqashid sunnah. Among several maqasid sunnah, there is maqoshid riayat-al-Mujtama' or the aim of developing society, which contains values that lead to the development of society. This study will use a qualitative methodology by analyzing the values contained in the maqashid riayat-al-Mujtama and then bringing them into education to find their suitability as a basis for Progressive Islamic Education. The conclusion of this study is that maqosid riayat-al-mujtama, which contains social values in the form of freedom, helping each other in goodness, justice, equality, mutual love, and care, can be used as a philosophical basis for progressive Islamic education.